Variation of Time and Ethanol Solvent Concentration Of Kinetic Maceration Tannin Extraction From Aromatic Areca Catechu - Hibrah Hibrah; Ferry Ikhsandy; Agung Kurnia Yahya; Rosalina Rosalina (Jurnal Ilmiah Teknik Kimia, 2022)
Aromatic areca catechu is one of the main agro commodities in West Sumatra. It contains tannin which are valuable compounds that are widely used in the textile industries, leather product manufacturing, or furniture industries. Utilization of tannin extraction from the aromatic betel nut is expected to increase its economic value. This study aims to extract tannin through kinetic maceration methods by varying the maceration duration of 1,2,3,4, and 5 hours; and varying the solvent concentration of ethanol 35%, 50%, 65%, 80%, and 96%. The scented areca nut powder used has a mesh size of e” 20, the stirring speed 450 rpm and the temperature kept constant at 45 oC. The extraction results were then concentrated and tested by UV-Vis spectrophotometric analysis with a standard solution of tannic acid. Optimal yield value is 3.750%  identified at maceration length of 2 hours with a solvent concentration of 65% ethanol.